Educational Attainment and Earnings Inequality in Eight Nations - Dennis Hal Sullivan; Timothy Michael Smeeding (Luxembourg Income Study (LIS), 1997)
This paper investigates the relationship between educational attainment and earnings inequality in eight nations using the Luxembourg Income Study (LIS) database. Although the results should be considered exploratory rather than definitive until verified and qualified by more detailed comparative studies, two basic conclusions can be simply stated. First, among advanced economies there is no obvious relationship between the degree of earnings inequality and the percentage of the labor force attaining higher levels of education. The second conclusion is less agnostic: there is a clear positive correlation between the earnings differentials associated with greater educational attainment and the extent of earnings inequality.
Keywords: 330; Einkommensverteilung; Berufsbildung; USA; Kanada; Australien; Deutschland; Niederlande; Schweden; Ungarn